2008
DOI: 10.1038/oby.2008.331
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Infection of Cultured Adipocytes Results in an Inflammatory Phenotype

Abstract: Infection with Trypanosoma cruzi, the etiologic agent of Chagas disease is accompanied by an intense inflammatory reaction. Our laboratory group has identified adipose tissue as one of the major sites of inflammation during disease progression. Because adipose tissue is composed of many cell types, we were interested in investigating whether the adipocyte per se was a source of inflammatory mediators in this infection. Cultured adipocytes were infected with the Tulahuen strain of T. cruzi for 48-96 h. Immunobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
65
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 40 publications
5
65
0
2
Order By: Relevance
“…We previously demonstrated that ECM results in cognitive impairment associated with white matter damage in mice [43], [45]. The protein tau, a substrate of GSK3β, interacts with microtubules and is associated with early memory loss and cognitive dysfunction in neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…We previously demonstrated that ECM results in cognitive impairment associated with white matter damage in mice [43], [45]. The protein tau, a substrate of GSK3β, interacts with microtubules and is associated with early memory loss and cognitive dysfunction in neurodegenerative diseases.…”
Section: Resultsmentioning
confidence: 99%
“…Infection with Trypanosoma cruzi, the etiologic agent of Chagas disease, involves adipose tissue. Adipocytes can be infected directly, and expression of IL-1b, IFN-g, TNF-a, CCL2, CCL5, CXC chemokine ligand 10 (CXCL10), TLR2, and TLR9 is increased after infection, whereas expression of adiponectin and PPARg is decreased [60]. Thus, adipose tissue contributes to the inflammatory response observed in Chagas disease.…”
Section: Reviewmentioning
confidence: 97%
“…Both caveolin-1 and PPARγ are among the group of proteins in which mutation results in lipodystrophy (Rochford, 2010). Both are downregulated in cultured adipocytes during bacterial infection (Nagajyothi et al, 2008) and in a variety of cell types by TGFβ treatment (Wang et al, 2006; Tourkina et al, 2010; Wei et al, 2010). However, data from our lab and others suggests that TGFβ does not decrease PPARγ levels in monocytes (Figure 4, Kintscher et al, 2002).…”
Section: Discussionmentioning
confidence: 99%